Insulin Resistance in Gestational Diabetes Mellitus and Its Association With Anthropometric Fetal Indices - Tuan Dinh Le; Tien Minh Bui; Trinh Hien Vu; Nga Phi Thi Nguyen; Hoa Thanh Thi Tran; Son Tien Nguyen; Lan Ho Thi Nguyen; Manh Van Ngo; Hoang Huy Duong; Binh Thanh Vu; Hoa Trung Dinh; Binh Nhu Do; et al. (Clinical Medicine Insights: Endocrinology and Diabetes, 2022)
Background: In pregnant women with gestational diabetes mellitus (GDM), insulin resistance (IR) increases the risk of developing manifest type 2 diabetes mellitus and is associated with complications in both mother and fetus. Objectives: This research aimed to evaluate the associations between IR evaluated by 3 indices (namely updated homeostasis model assessment model (HOMA2), QUICKI, and McAuley’s index) and the diabetes risk factors and the fetal growth indices in Vietnamese women with GDM. Methods: A cross-sectional descriptive study was conducted on 370 women with GDM and 40 healthy pregnant women from January 2015 to May 2019. IR was calculated by HOMA2 (HOMA2-IR), QUICKI, and McAuley’s index. Fetal anthropometric measurements were assessed via ultrasound which was performed and interpreted by ultrasound experts. Results: In the simple regression analysis, McAuley’s index illustrated had statistically significant correlations to the highest number of risk factors of diabetes mellitus compared with HOMA2-IR and QUICKI indices. Moreover, McAuley’s index correlated statistically significantly to the highest number of fetal ultrasound measurements factors such as including biparietal diameter (BPD) ( r  = −0.271, P  < .001), head circumference (HC) ( r  = −0.225, P  < .001), abdominal circumference (AC) ( r  = −0.214, P  < .001), femur length (FL) ( r  = −0.231, P  < .001), estimated fetal weight (EFW) ( r  = −0.239, P  < .001) and fetal estimated age ( r  = −0.299, P  < .001). In the multivariable analysis, the McAuley’s index contributed the greatest to AC (Standardized B of −0.656, P  < .001). Conclusion: The McAuley’s index was significantly associated with a higher number of more risk factors for diabetes mellitus as well as fetal ultrasound sonography findings measurements than compared with HOMA2-IR and QUICKI indices.